Susceptibilidad antimicrobiana de Escherichia coli causante de infección de vías urinarias en usuarios del Hospital Isidro Ayora, Loja - Torres Aguilar, Sthefany Cecibel (2018)
Urinary tract infection (UTI) is one of the most frequent bacterial infections in any age, with predominance in women with high probability of recurrence due to reinfections with germs other than the first manifestation; UTI involves the growth of germs in the urinary tract, where Escherichia coli is the most frequently isolated species in urinary tract infections at any age, with 95% of cases. (Pigrau Serrallach, 2013). This descriptive and cross-sectional study, called "Susceptibilidad antimicrobiana de Escherichia coli causante de infección de vías urinarias en usuarios del Hospital Isidro Ayora, Loja"; aimed to know the antimicrobial susceptibility of Escherichia coli and classify the resistant strains of the same according to age, sex and area of health service; the universe was all urine samples with orders of urine culture, which was 591, of which 173 strains of Escherichia coli were isolated in which the antimicrobial susceptibility was identified and determined by the automated method; screening for beta-lactamase production was performed according to the criteria of table 3A and 3C of document M100-S28 of the CLSI and phenotypically confirmed by criteria of the same table, resistance was presented in trimetropin sulfamethoxazole with 53.03% and ampicillin / sulbactam with 42.46% and of the Escherichia coli samples, 30 showed ESBL resistance mechanism (extended spectrum beta-lactamasmas) and one AmpC type case; this was found more frequently in women than in men in adulthood (20 to 59 years) and older adults (over 60 years); in the emergency area more frequently. Key words: Escherichia coli, (UTI) Urinary tract infection, antimicrobial susceptibility, ESBL.